Improvement of Construction Workers' Skills in House Construction in Pinrang Regency - Adnan, Adnan; Wakkang, Hamka; Abibullah, Abibullah; Yusuf, Muh. (Jurnal Pengabdian Masyarakat, 2024)
Purpose: This community service initiative aims to provide training to construction workers and their assistants in Pinrang Regency, South Sulawesi, addressing the issue of inadequate autodidactic skills. The research is significant for ensuring compliance with construction standards, reducing risks of structural failures. Method: The study involves structured training sessions focused on proper construction practices, with pre- and post-training assessments to measure skill improvement and participant feedback for refinement. Practical Applications: The findings have practical implications for the construction industry, enhancing project outcomes and structural integrity in remote areas. This training fosters better management practices and benefits community infrastructure. Conclusion: The training significantly improves the skills of construction workers, emphasizing the need for formal education to achieve safety and compliance with standards. This initiative promotes long-term benefits for the region’s construction sector.